A ANALISIS PEMECAHAN MASALAH SISWA DALAM MENYELESAIKAN SOAL DITINJAU DARI KECEMASAN MATEMATIS : ANALISIS PEMECAHAN MASALAH SISWA BERDASARKAN KECEMASAN MATEMATIS - Rani Hidayat; Agus Jaenudin; Tita Rosita, Neneng (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2024)
Students' prior knowledge at a superficial level is reviewed when they solve mathematical problems. This step is crucial to strengthen their knowledge and provide the necessary information required to solve the problems. The purpose of this study is to analyze how elementary school students' problem-solving abilities are affected by their levels of math anxiety. This research employs a qualitative descriptive analysis method with data collection techniques including tests and non-test methods, namely questionnaires and descriptive test questions. The non-test technique, in the form of a questionnaire, is used to assess students' levels of math anxiety, while the test technique, consisting of descriptive questions, is utilized to evaluate students' mathematical problem-solving abilities. The sample for this study consisted of 37 students. The results showed that students with low and very low levels of math anxiety demonstrated excellent mathematical problem-solving abilities. Students with moderate math anxiety exhibited good problem-solving abilities. Students with high math anxiety displayed adequate problem-solving abilities. Meanwhile, students with very high math anxiety showed poor mathematical problem-solving abilities. Keywords: Mathematical Problem-Solving Ability, Math Anxiet